2023
DOI: 10.1007/s11096-023-01592-y
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with underreporting of adverse drug reactions by patients: a systematic review

Catarina Costa,
Patricia Abeijon,
Daniela A. Rodrigues
et al.

Abstract: Background Spontaneous reporting is the most used method to monitor post-marketing safety information. Although patient involvement in spontaneous reporting has increased overtime, little is known about factors associated with patients’ adverse drug reaction (ADR) reporting. Aim To identify and assess the sociodemographic characteristics, attitudes and knowledge that influence spontaneous reporting and the reasons associated with ADR underreporting by pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 71 publications
0
8
1
Order By: Relevance
“…Regarding educational status, higher educational levels were associated with the presence of ADEs. This association has not been reported in other leprosy studies; however, higher educational levels could lead to a better understanding of the occurrence of drug-related symptoms and, thus, increase the probability of a patient reporting the symptoms, as was described recently by Costa et al (2023) [28]. Other studies have shown that higher educational levels in different diseases could help medication intake and reduce ADEs [32,33].…”
Section: Discussionmentioning
confidence: 73%
See 1 more Smart Citation
“…Regarding educational status, higher educational levels were associated with the presence of ADEs. This association has not been reported in other leprosy studies; however, higher educational levels could lead to a better understanding of the occurrence of drug-related symptoms and, thus, increase the probability of a patient reporting the symptoms, as was described recently by Costa et al (2023) [28]. Other studies have shown that higher educational levels in different diseases could help medication intake and reduce ADEs [32,33].…”
Section: Discussionmentioning
confidence: 73%
“…Previous studies have demonstrated that older age groups are more likely to experience ADEs [ 28 ]. In the present study, we demonstrated that the older participants (>47 years) had more ADEs than younger ones.…”
Section: Discussionmentioning
confidence: 99%
“…Uncertainty surrounding causal relationships is a further contributing factor to underreporting in spontaneous systems. Additionally, fear of medicolegal consequences, alongside overall clinician indifference is known to further discourage consistent reporting (85,88,89).…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, some healthcare providers do not report because of the fear of legal consequences, which was also seen in several studies. [55][56][57][58]…”
Section: Strength Of the Associationmentioning
confidence: 99%